1997
DOI: 10.1242/jcs.110.5.589
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the membrane-type matrix metalloproteinase MT1-MMP in osteoclasts

Abstract: The osteoclasts are the cells responsible for bone resorption. Matrix metalloproteinases (MMPs) appear crucial for this process. To identify possible MMP expression in osteoclasts, we amplified osteoclast cDNA fragments having homology with MMP genes, and used them as a probe to screen a rabbit osteoclast cDNA library. We obtained a cDNA of 1,972 bp encoding a polypeptide of 582 amino acids that showed more than 92% identity to human, mouse, and rat membrane-type 1 MMP (MT1-MMP), a cell surface proteinase beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“… 147 MT1-MMP-knockout (KO) mice usually die couple of months after birth, and display a severe phenotype that includes delayed ossification, unclosed sutures and unremoved cartilage. 148 MMP-14 is highly expressed on osteoclast podosomes, 149 and it digests interstitial collagen as well as other ECM molecules. 150 MMP-9-KO mice showed reduced osteoclast invasion into the core of developing bones, 151 and in vitro, osteoclasts lacking MMP9 did not migrate.…”
Section: Osteoclastsmentioning
confidence: 99%
“… 147 MT1-MMP-knockout (KO) mice usually die couple of months after birth, and display a severe phenotype that includes delayed ossification, unclosed sutures and unremoved cartilage. 148 MMP-14 is highly expressed on osteoclast podosomes, 149 and it digests interstitial collagen as well as other ECM molecules. 150 MMP-9-KO mice showed reduced osteoclast invasion into the core of developing bones, 151 and in vitro, osteoclasts lacking MMP9 did not migrate.…”
Section: Osteoclastsmentioning
confidence: 99%
“…Cells form different membrane protrusions to explore the surrounding ECM, such as filopodia [ 284 ] and lamellipodia [ 285 ]. MMP-14 has been reported to be also localized to filopodia [ 286 ] and lamellipodia, where it indirectly associates with the actin cytoskeleton by binding with its HPX domain to the hyaluronan receptor CD44 [ 287 , 288 , 289 , 290 ]. These membrane protrusions are mechanically stabilized by adhesive matrix contacts, to which several adhesome components are recruited, e.g., regulators of lamellipodial cell migration, Rac, WASp, Arp2/3, arpin, lamellipodin, WAVE, Mena, and Ena/VASP family members.…”
Section: Cellular Adhesome Structures In the Tmementioning
confidence: 99%
“…Rac1 augments dimer formation of MT1-MMP and proMMP-2 activation at lamellipodia Using the chimera construct, we next investigated whether there are any factors that might regulate the dimer formation of MT1-MMP on the cell surface. Since it has been reported that MT1-MMP is localized at the lamellipodia structure in walking osteoclasts (Sato et al, 1997), we looked at the effect of a constitutively active form of the small GTPase Rac1 (V12Rac1, Rac1DA) on dimer formation as a GTP-bound form of Rac1 stimulates the generation of lamellipodia in cells (Michiels et al, 1995). MT1-F/NGFR was co-expressed with Rac1DA in COS1 cells and the phosphotyrosine signal was monitored.…”
Section: Mt1-mmp Forms a Homophilic Complex On The Cell Surfacementioning
confidence: 99%